Validação de intervenções de enfermagem para o equilíbrio postural de pessoas idosas hospitalizadas - França, Larrissa Mariana Bezerra (2022)
Introduction: The hospitalization of elderly people represents a greater risk of falls in this group, due to the association of the functional decline of aging and the reduction of postural balance with prolonged hospital stay. For this reason, nursing care is fundamental, and the nursing process, a methodological instrument of this care, will help to implement preventive and effective interventions to improve the balance of these elderly people. Objective: To validate nursing interventions for postural balance in hospitalized elderly people. Method: This is a methodological research, developed in three phases: integrative review, cross mapping with the Nursing Interventions Classification and content validation by nurse judges. The Content Value Index was considered ≥ 0.80. Data were collected from February 2021 to January 2022, and the analysis was performed using descriptive statistics using the Statistical Package for Social Science version 26.0 program. The research was approved by the Ethics Committee of the Health Sciences Center of the Federal University of Paraíba, under opinion number 4,473,214. Results: In the integrative review, nine articles and 29 nursing care were found; 29 nursing care was mapped with 14 NIC interventions and 56 activities using the NANDA-I/NIC connection. In this mapping, it was found that the most recurrent interventions were: “Therapy with exercise: balance” and “Medication Control”, both with nine activities, and “Fall Prevention”, with seven activities. In the validation phase, nine judge nurses participated who analyzed the 14 interventions as valid: ten were classified as suggested according to the NANDA-I/NIC connection, because they achieved a CVI of ≥ 0.80, and four, as additional options, with CVI of 0.79 and ≥ 0.50. In this phase, the interventions “Exercise Therapy: ambulation”, “Exercise Therapy: mobility” and “Promotion of exercise: training for strengthening” stood out. Conclusion: All nursing interventions mapped to the postural balance of hospitalized elderly people, with the purpose of preventing falls, were validated by the nurse judges. It is hoped that this result can be used, in practice, by nursing professionals, in order to implement validated preventive interventions for the balance of hospitalized elderly people and ensure a safe and good quality nursing therapeutic plan.